2015
DOI: 10.2460/javma.247.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Venous blood gas analytes during isoflurane anesthesia in black-tailed prairie dogs (Cynomys ludovicianus)

Abstract: Examination of prairie dogs often requires general anesthesia, with isoflurane currently the inhalation agent of choice. Results suggested respiratory acidosis and relative azotemia may occur during isoflurane anesthesia of prairie dogs. Given the increased risk associated with anesthesia in small mammals and the propensity for respiratory disease in prairie dogs, insight into physiologic changes associated with isoflurane anesthesia in healthy prairie dogs can aid in perioperative evaluation and anesthetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…17 Given their fractious nature, chemical immobilization or general anesthesia is often necessary for examination or diagnostic procedures in prairie dogs. 9,12 Inhalant anesthetic agents are most commonly used in anesthetic protocols; however, few studies evaluate injectable anesthetic agents in this species. 9,12 Isoflurane is an anesthetic gas that is frequently recommended for use in prairie dog anesthesia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…17 Given their fractious nature, chemical immobilization or general anesthesia is often necessary for examination or diagnostic procedures in prairie dogs. 9,12 Inhalant anesthetic agents are most commonly used in anesthetic protocols; however, few studies evaluate injectable anesthetic agents in this species. 9,12 Isoflurane is an anesthetic gas that is frequently recommended for use in prairie dog anesthesia.…”
mentioning
confidence: 99%
“…9,12 Inhalant anesthetic agents are most commonly used in anesthetic protocols; however, few studies evaluate injectable anesthetic agents in this species. 9,12 Isoflurane is an anesthetic gas that is frequently recommended for use in prairie dog anesthesia. 23 Several studies evaluate isoflurane in this species, which is typically delivered via chamber or facemask due to difficulty in performing endotracheal intubation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,15,18 Chemical immobilization is frequently required for examination and diagnostic testing of prairie dogs, with inhalant anesthetic agents commonly used for anesthesia. 7,11 Isoflurane is a gas anesthetic commonly used in many rodent procedures and has generally been recommended for use in prairie dogs. 7,11 However, a comparative report showed that rodents and other small mammals had a significantly (10% to 22%) higher anesthesia-related mortality rate than other anesthetized species.…”
mentioning
confidence: 99%
“…7,11 Isoflurane is a gas anesthetic commonly used in many rodent procedures and has generally been recommended for use in prairie dogs. 7,11 However, a comparative report showed that rodents and other small mammals had a significantly (10% to 22%) higher anesthesia-related mortality rate than other anesthetized species. 4 Changes in T4 concentration (and other thyroid hormones) can lead to unstable anesthesia and increase the associated risks.…”
mentioning
confidence: 99%